SISTEM INFORMASI PEMASARAN RANI BUTIK MENGGUNAKAN ELECTRONIC COMMERCE DENGAN MODEL BUSINESS to CONSUMER - Kasmi Kasmi; Rani Erinika Putri (Jurnal Signaling, 2022)
E-commerce is a form of utilization of computer information technology that is used especially in the trade business where consumers will be facilitated in searching for data/information as well as buying and selling goods. It is hoped that it can become a promotional media for Rani Boutique that is able to present data and information that can be accessed via the internet. The benefits of making this system can provide convenience to business owners in organizing, and processing data, and information and increasing sales effectiveness. The benefits of this system can provide convenience to the people of Sukoharjo, Pringsewu in particular and outsiders in general in terms of getting information about Rani Boutique. This system was built using the waterfall development method which includes the stages of analysis, design, coding, implementation and maintenance.